Intervention with the Screening Tool of Older Persons Potentially Inappropriate Prescriptions/Screening Tool to Alert Doctors to Right Treatment Criteria in Elderly Residents of a Chronic Geriatric Facility: A Randomized Clinical Trial. Issue 9 (September 2014) - Frankenthal, Dvora; Lerman, Yaffa; Kalendaryev, Edward; Lerman, Yehuda
<x xml:space="preserve">Abstract</x> Objectives To assess the effect of a Screening Tool of Older Persons potentially inappropriate Prescriptions/Screening Tool to Alert doctors to Right Treatment (STOPP/START) medication intervention on clinical and economic outcomes. Design Parallel‐group randomized trial. Setting Chronic care geriatric facility. Participants Residents aged 65 and older prescribed with at least one medication (N = 359) were randomized to receive usual pharmaceutical care or undergo medication intervention. Intervention Screening medications with STOPP/START criteria followed up with recommendations to the chief physician. Measurements The outcome measures assessed at the initiation of the intervention and 1 year later were number of hospitalizations and falls, Functional Independence Measure (FIM), quality of life (measured using the Medical Outcomes Study 12‐item Short‐Form Health Survey), and costs of medications. Results The average number of drugs prescribed was significantly lower in the intervention than in the control group after 1 year (P < .001). The average drug costs in the intervention group decreased by 103 shekels (US$29) per participant per month (P < .001). The average number of falls in the intervention group dropped significantly (P = .006). Rates of hospitalization, FIM scores, and quality of life measurements were similar for both groups. Conclusion Implementation of STOPP/START criteria reduced the number of medications, falls, and costs in a geriatric facility. Their incorporation in those and similar settings is recommended.